Building Effective Drinking Water Management Policies In Rural Africa: Lessons From Northern Uganda - Opio, Christopher (CIGI-Africa Initiative, 2012)
The importance of providing clean, safe drinking water and sanitation to rural inhabitants of developing countries is widely recognized. The United Nations (UN) General Assembly, for instance, declared 2008 the International Year of Sanitation, and the World Bank has been increasing financial assistance to developing countries in support of water supply and sanitation improvements (Cho, Ogwang and Opio, 2010). Despite the Millennium Development Goal (MDG) to reduce, by half, the number of people without sustainable access to clean and safe drinking water and basic sanitation by 2015 (Cho, Ogwang and Opio, 2010; Opio, 2010), most countries in Sub-Saharan Africa are not on track to meet the widely adopted deadline (Harvey, 2007; United Nations Children’s Fund [UNICEF], 2012; Abenaitwe, 2012).